Perencanaan Kebutuhan SDM (Manajemen dan Operasional) dan Rumusan Pengembangan SDM - Fajar Dio Wahyu Tri Amukti; Agung Winarno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Human resource (HR) planning and development is an important foundation in supporting the achievement of strategic organizational goals. This article comprehensively discusses the HR needs planning process in the managerial and operational context, as well as sustainable HR development strategies. The method used is a literature study with a descriptive approach to explore concepts, theories, and best practices in HR management. The results of the study indicate that HR planning not only includes recruitment and training, but also talent management, career development, and structured performance evaluation. On the other hand, HR development strategies focus on improving competencies through technical training, leadership development, and soft skills to face changes in the business environment. The synergy between planning, operational implementation, and HR development is very important to form an adaptive, competitive, and sustainable organization.